2021
DOI: 10.3390/polym14010080
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of Ionic Polymer-Metal Composite Actuators with Polyethylene Oxide

Abstract: Current ionic polymer-metal composite (IPMC) always proves inadequate in terms of large attenuation and short working time in air due to water leakage. To address this problem, a feasible and effective solution was proposed in this study to enhance IPMC performance operating in air by doping polyethylene oxide (PEO) with superior water retention capacity into Nafion membrane. The investigation of physical characteristics of membranes blended with varying PEO contents revealed that PEO/Nafion membrane with 20 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Such a possibility is of great interest from a fundamental point of view, and also opens up a number of interesting applications in various industrial fields. This is why the number of publications devoted to the study of Nafion is constantly growing (see, e.g., [2][3][4][5][6][7][8][9], related to the articles dedicated to the study of various properties of Nafion and issued in 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Such a possibility is of great interest from a fundamental point of view, and also opens up a number of interesting applications in various industrial fields. This is why the number of publications devoted to the study of Nafion is constantly growing (see, e.g., [2][3][4][5][6][7][8][9], related to the articles dedicated to the study of various properties of Nafion and issued in 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In general, ionic polymer-metal composites consist of a polymeric ion exchange membrane with negative ions fixed on interconnected clusters, fully swollen by water, and a thin layer of noble metal as electrodes, Figure 21. By applying a voltage on this EAP, the hydrated cation begins to move freely towards the cathode through the polymer membrane, which provides channels for their movements; and then cation accumulates on the cathode, causing swelling of the actuator and its bending, Figure 21 [52,72]. The needed low driving voltage (1-5 V), the high ionic conductivity of the electrolyte, fast response, and large deformation are considered the main advantages of this EAP type.…”
Section: Ionic Polymer-metal Compositesmentioning
confidence: 99%
“…The main problem of the water-based ionic polymer-metal actuator, which reduces both actuator efficiency and its lifetime, is the leakage of the water molecules into the cracks of the metal electrodes as a result of the electrolysis and the evaporation of water in the presence of air [77]. In the reference [72], the authors tried to solve this problem by adding polyethylene oxide (PEO) into a Nafion matrix, which has a significant capacity for water retention. They showed that using PEO by 20 wt.% led to a reinforcement of the electromechanical performances and a restriction of the displacement attenuation of the actuator.…”
Section: Ionic Polymer-metal Compositesmentioning
confidence: 99%
“…The non-feedback method for eliminating the “back relaxation” effect of non-patterned IPMCs by using a relatively high-frequency disturbance is proved in [ 20 ]. The doping of polyethylene oxide PEO reinforced electromechanical performances and restrained displacement attenuation of the resultant IPMC [ 21 ]. The IPMC-Li samples are used as actuators because of their rapid actuation movement, large displacement and absence of apparent back-relaxation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The IPMCs are characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, cross-sectional morphology and in term of electromechanical performances [ 28 , 29 ]. The IPMCs applications can be found in [ 21 , 30 , 31 , 32 ] since they are the most promising development materials. Although many models are useful for studying the capabilities of electroactive polymers and characterization bench [ 30 , 31 ] this article focuses on design of experimental laboratory stand and characterization of IPMCs materials.…”
Section: Introductionmentioning
confidence: 99%